Pravo in ekonomija: Pravo, ekonomija in epidemija - Repas, Martina (2022)
Law and Economics: Law, Economics and Epidemic. The Covid-19 epidemic significantly affected all segments of life: education, work, health, business, functioning of important institutions, etc. The collection of scientific papers highlights various segments and problems that have arisen due to the epidemic and the lockdown as a consequence. It discusses the impact of the epidemic on the link between strategic and development planning and the budget planning, on intellectual property rights in terms of more efficient provision of medicines and vaccines, on studies in terms of providing copyrighted material and the introduction of distance learning. The role of lockdown in the development of new alcohol marketing technologies is particularly emphasized, as well as the consequences of the derogation of rights during the epidemic and thus inaccessibility to public administrative services, economic and business uncertainty in the euro area, which was greatest at the beginning of the crisis, and the possibility of inter-state actions before the EU Court of Justice as a mechanism of protection of fundamental human values.
Keywords: law; economic; epidemic; Covid-19; intellectual property; distance learning; economy; new technologies; public services; state budget; inter-state actions; alcohol